Gender Norms and the Motherhood Penalty: Experimental Evidence from India - Arjun S. Bedi; Tanmoy Majilla; Matthias Rieger (Institute of Labor Economics (IZA), 2018)
This paper uses a field experiment to study the effect of perceived gender norms on the motherhood penalty in the Indian labor market. We randomly reported motherhood on fictitious CVs sent to service sector job openings. We generated exogenous variation in gender norms by prominently signaling patrilineal or matrilineal community origins of applicants. Employers are less likely to callback mothers relative to women or men without children, but only if they are of patrilineal origin. Mothers of matrilineal origin face no such penalty. We discuss the results in relation to the competing influence of ethnicity, the Indian context and theories of discrimination.
Keywords: J16; J71; 330; gender; culture; motherhood penalty; ethnic discrimination; field experiment; India